Prevalence of Schistosoma mansoni and its clinical relevance at a primary health care level in rural lake zone of Tanzania: a cross sectional study (Tanzania Medical Journal, 2016)
Introduction Intestinal schistosomiasis is still endemic in most countries in sub Saharan Africa including Tanzania. It is associated with unacceptably high morbidity and mortality especially due to its long term complications. These complications could potentially be prevented through early diagnosis and timely treatment of Schistosoma mansoni infection. However, in Lake Zone only a small proportion of patients present to tertiary level hospital in early stages of the disease and schistomal status at primary health care level is not described in Lake Zone. The aim of this study was to determine the prevalence of Schistoma mansoni and its clinical relevance at a primary health care level.Materials and methodsA cross sectional study including all patients attending Sengerema DDH with abdominal pain and/or diarrhea was done. Their stool samples were examined by routine wet mount preparation and the data of study interest were analyzed including stool sample results, demographic data, clinical symptoms and risks for Schistosomal exposure using stata version 12 to determine the prevalence of Schistosoma mansoni in this study population.ResultsA total of 1255 stool samples were examined parasitologically for presence of intestinal parasites. Most of the study participants were females 783(62.39%) with a mean age of 30 (IQR 2-80) years. Of the 1225 stool samples examined, 561 (44.7%) were parasitologically positive for intestinal parasites where Schistosoma mansoni was recovered in 141 (11.24%) of the study participants being the second most common intestinal parasite after Entamoeba histolytica. Of the positive stool samples Schistosoma mansoni was found in 25.1% of the samples and was strongly associated with a male gender (OR=1.5, p=0.017), age younger than 20 years (OR= 3.4, p<0.001), and being involved in fishing (OR=1.9, p=0.043) and rice pad activities (OR=3.1, p<0.001).Conclusions The current study indicates that Schistosoma mansoni transmission still occurs in Lake Zone, however probably the symptoms due to intestinal Schistosoma infections are frequently common among young people. On clinical aspects these findings are important suggesting that transmission of S. mansoni could significantly be reduced by praziquantel (PZQ) mass drug administration (MDA) targeting those at risk including ages below 20years, but this may need a sustained and more regular frequent PZQ doses a year.